Tracing founder haplotypes of Japanese apple varieties: application in genomic prediction and genome-wide association study. (1st March 2021) - Minamikawa, Mai F; Kunihisa, Miyuki; Noshita, Koji; Moriya, Shigeki; Abe, Kazuyuki; Hayashi, Takeshi; Katayose, Yuichi; Matsumoto, Toshimi; Nishitani, Chikako; Terakami, Shingo; Yamamoto, Toshiya; Iwata, Hiroyoshi
Abstract: Haplotypes provide useful information for genomics-based approaches, genomic prediction, and genome-wide association study. As a small number of superior founders have contributed largely to the breeding history of fruit trees, the information of founder haplotypes may be relevant for performing the genomics-based approaches in these plants. In this study, we proposed a method to estimate 14 haplotypes from 7 founders and automatically trace the haplotypes forward to apple parental (185 varieties) and breeding (659 F1 individuals from 16 full-sib families) populations based on 11, 786 single-nucleotide polymorphisms, by combining multiple algorithms. Overall, 92% of the single-nucleotide polymorphisms information in the parental and breeding populations was characterized by the 14 founder haplotypes. The use of founder haplotype information improved the accuracy of genomic prediction in 7 traits and the resolution of genome-wide association study in 13 out of 27 fruit quality traits analyzed in this study. We also visualized the significant propagation of the founder haplotype with the largest genetic effect in genome-wide association study over the pedigree tree of the parental population. These results suggest that the information of founder haplotypes can be useful for not only genetic improvement of fruit quality traits in apples but also for understanding the selection history of founder haplotypes in the breeding program of Japanese apple varieties.